Differential Scanning Calorimetry and Fourier Transform Infrared Analyses of Filled Polymer Pellets - Nawi, Nazim Basir; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
This study investigates the effects of filler incorporation on the chemical structure and thermal properties of polymer masterbatch pellets using Fourier Transform Infrared (FTIR) spectroscopy and Differential Scanning Calorimetry (DSC). FTIR analysis revealed that both with and without filler samples are based on a polyolefin matrix, as confirmed by the characteristic C–H stretching vibrations at 2916–2921 cm⁻¹ and 2849–2855 cm⁻¹. However, the masterbatch with filler exhibited additional absorption bands within the regions of 1600–1500 cm⁻¹, 1260–1150 cm⁻¹, and 1110–1010 cm⁻¹, indicating the presence of oxygen- and nitrogen-containing functional groups associated with surface-treated fillers, compatibilizers, or dispersing agents. DSC analysis showed that both samples followed the expected thermal transition sequence of Tg < Tc < Tm. The masterbatch with filler exhibited a lower crystallization enthalpy (0.62 J/g) compared to the masterbatch without filler (0.96 J/g), suggesting reduced crystallization ability due to restricted polymer chain mobility caused by the filler particles. In addition, the melting temperature (Tm) of the masterbatch with filler was slightly lower (123.32°C) than that of the masterbatch without filler (123.65°C), indicating disruption of crystalline perfection within the polymer matrix. Overall, the findings demonstrate that filler incorporation significantly modifies the chemical structure and thermal behaviour of the masterbatch pellets while maintaining the fundamental characteristics of the polyolefin-based polymer system.